PARENTING DAN PERKEMBANGAN ANAK USIA DINI DI ERA DUNIA DIGITAL 5.0 - Nazila Ratna Anindita (Universitas Darunnajah, 2024)
We can see that the development of children in Indonesia now is very sad because we know that many children do not have good character and can support this nation in the current era. The development of children today is in the development of good character and also values. such as politeness, honesty and also religious values. This research aims to get an overview of parental parenting regarding current developments for young children. This method uses a qualitative descriptive method of case studies of problems in the surrounding environment. The results and discussion show that children at an early age don't know anything, they can only imitate what they see and what they hear, that's why there are so many children in the current era who don't have good moral character in the family or around them, because lack of supervision from parents so they only imitate what they see and listen to without knowing good and bad because children at an early age cannot filter what enters their minds and those who can filter it all are parents or parenting